Pengaruh Budaya Organisasi terhadap Kinerja Karyawan di BPJS Ketenagakerjaan Bangkalan - Agustin Pratiwi; Filsa Soraya; Mochammad Isa Anshori (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The influence of organizational culture on employee performance at BPJS Employment Bangkalan is discussed in this research. Employees can be inspired, motivated, and guided to achieve company goals effectively through a strong and healthy organizational culture. Based on previous research, this study tries to investigate how company culture influences employee performance. Literature review is the research method used. This approach uses various literature sources, including books, journals, and other scientific publications, to collect data. The findings of this research can be used to find out how much influence organizational culture at BPJS Employment Bangkalan has on employee performance.